Development of coffee pulp extract-incorporated chitosan film and its antimicrobial and antioxidant activities - Jaisan, Chalalai; Punbusayakul, Niramol (Asia-Pacific Journal of Science and Technology, 2016)
The aim of this work was to preliminary develop a coffee pulp extract- incorporated chitosan film. Coffee pulp (CP) was obtained from Doi Chaang Original Co. Ltd, Chiang Rai, Thailand. The CP was extracted with distilled water at the CP-to-distilled water ratio of 1:2, and then the mixture was filtered, centrifuged and dried by freeze drying to obtain the dried coffee pulp extract powder (CPE). Chitosan (CH) film incorporated with various concentrations of CPE (0-1.0 % w/v) was prepared by casting method and dried at different temperatures (ambient, 30 and 40 oC). The antimicrobial activity of the films against some potent foodborne microorganisms (Bacillus cereus KCCM 40133, B. subtilis KCCM 11316, Escherichia coli KCCM 21052 and Pseudomonas fluorescence KCCM 11362) was evaluated by disc diffusion method. The antioxidant activity (DPPH assay) and physical properties (water vapor permeability (WVP), solubility and color (L*, a* and b*) of the film were determined. There was no inhibitory effect observed when the CH film without CPE was tested by disc diffusion method. The antimicrobial and antioxidant activities of the CPE-CH films significantly increased with the increasing CPE concentration (p≤0.05). The WVP and solubility of the CH film without the CPE was higher than those of the CPE-CH film. With the increasing CPE concentration in the CH matrix, the WVP and solubility of the CPE-CH film significantly decreased (p≤0.05). These results indicate that the CPE-CH film could be applied as an antimicrobial and antioxidant food packaging.